PENGARUH PEMBERIAN SENAM LANSIA DAN STRETCHING KNEE TERHADAP KEMAMPUAN FUNGSIONAL PADA OSTEOARTHRITIS KNEE - Metty Herawaty (Poltekkes 'Aisyiyah Banten, 2022)
Background: OA (Osteoarthritis) is a degenerative joint disease, this knee joint disease tends to increase due to aging. Osteoarthritis affects 3 knee joints (medial, lateral, and patellofemoral joint) and usually Osteoarthritis will develop slowly which is about more than 10-15 years and the pain of Osteoathritis will interfere with daily life. There are several physiotherapy modalities, some examples of which are elderly exercise and knee stretching which are used to improve the functional ability of the elderly. Research Objectives: To find out a good exercise program to increase the functional activity of the elderly. Research Methods: this research method is narrative review research. Journal searches were conducted on online journal portals such as Google Scholar, PubMed, and Sciendirect. The results of the journal search found that 5 Elderly Gymnastics journals and 5 stretching knee journals were reviewed in this study. Conclusion : There is an effect of elderly exercise and knee stretching on improving the functional ability of the elderly as an effective intervention.